Sosialisasi Model Pembelajaran Deep Learning bagi Mahasiswa Pendidikan Jasmani [Socialization of Deep Learning Teaching Model for Physical Education Students] - Meikahani, Ranintya; Setyo Kriswanto, Erwin; Dwihandaka, Riky; Santoso, Nugroho Puji (Indonesia Berdaya, 2025)
Community Service Activity (PkM) with the theme of Socialization of the Deep Learning Learning Model was held by the Elementary School Physical Education Study Program (PJSD) FIKK UNY at the Faculty of Sports Science (FKOR) at Sebelas Maret University (UNS). The background of this activity is the importance of introducing the deep learning approach in PJOK education to shift the learning orientation from mere memorization toward deeper, critical, and meaningful understanding. The activity was conducted through socialization and interactive discussions with fourth-semester students of the Physical Education Program at FKOR UNS. The socialization focused on understanding the concept of deep learning, its application in physical education learning, and joint reflection on the potential and challenges of its implementation in elementary schools. The results of the activity showed that participants exhibited high enthusiasm and were able to grasp the essence of deep learning as an approach emphasizing the interconnectedness of concepts, the development of critical thinking skills, and the engagement of affective, cognitive, and psychomotor aspects. The discussions confirmed that this model is relevant for application in active, contextual, and meaningful PJOK learning. In conclusion, this socialization activity proceeded smoothly, was communicative, and made a positive contribution to enhancing the knowledge and readiness of prospective PJOK educators. The deep learning approach has the potential to serve as a foundation for cultivating innovative, reflective, and adaptive physical education teachers who can meet the needs of future generations.Abstrak. Kegiatan Pengabdian kepada Masyarakat (PkM) dengan tema Sosialisasi Model Pembelajaran Deep Learning dilaksanakan oleh Program Studi Pendidikan Jasmani Sekolah Dasar (PJSD) FIKK UNY di Fakultas Keolahragaan (FKOR) Universitas Sebelas Maret (UNS). Latar belakang kegiatan ini adalah pentingnya memperkenalkan pendekatan deep learning dalam pembelajaran PJOK guna menggeser orientasi belajar dari sekadar hafalan menuju pemahaman yang lebih mendalam, kritis, dan bermakna. Metode kegiatan dilaksanakan melalui sosialisasi dan diskusi interaktif dengan peserta mahasiswa semester 4 Program Studi Pendidikan Jasmani FKOR UNS. Sosialisasi difokuskan pada pemahaman konsep deep learning, penerapan dalam pembelajaran PJOK, serta refleksi bersama mengenai potensi dan tantangan implementasinya di sekolah dasar. Hasil kegiatan menunjukkan bahwa peserta memiliki antusiasme tinggi dan mampu memahami esensi deep learning sebagai pendekatan yang menekankan keterhubungan antar konsep, pengembangan keterampilan berpikir kritis, serta keterlibatan afektif, kognitif, dan psikomotor. Diskusi yang muncul menegaskan bahwa model ini relevan untuk diterapkan dalam pembelajaran PJOK yang aktif, kontekstual, dan bermakna. Kesimpulannya, kegiatan sosialisasi ini berjalan lancar, komunikatif, serta memberikan kontribusi positif dalam meningkatkan wawasan dan kesiapan calon pendidik PJOK. Pendekatan deep learning berpotensi menjadi pijakan dalam mencetak guru pendidikan jasmani yang inovatif, reflektif, dan adaptif terhadap kebutuhan generasi mendatang.